MCPIP-1 Restricts Inflammation via Promoting Apoptosis of Neutrophils - Dobosz, Ewelina; Wadowska, Marta; Kaminska, Marta; Wilamowski, Mateusz; Honarpisheh, Mohsen; Bryzek, Danuta; Potempa, Jan; Jura, Jolanta; Lech, Maciej; Koziel, Joanna (Frontiers in Immunology, 2021)
Monocyte chemoattractant protein-induced protein-1 (MCPIP-1) is a potent inhibitor of inflammatory response to pathogens. Acting as endonuclease against transcripts of inflammatory cytokines or transcription factors MCPIP-1 can significantly reduce the cytokine storm, thus limiting the tissue damage. As the adequate resolution of inflammation depends also on the efficient clearance of accumulated neutrophils, we focused on the role of MCPIP-1 in apoptosis and retention of neutrophils. We used peritoneal neutrophils from cell-specific MCPIP-1 knockout mice and showed prolonged survival of these cells. Moreover, we confirmed that MCPIP-1-dependent degradation of transcripts of antiapoptotic genes including BCL3, BCL2A1, BCL2L1, and for the first time MCL-1, serves as an early event in spontaneous apoptosis of primary neutrophils. Additionally, we identified previously unknown miRNAs as potential binding partners to the MCPIP-1 transcript and their regulation suggest a role in MCPIP-1 half-life and translation. These phenomena may play a role as a molecular switch that balances the MCPIP-1-dependent apoptosis. Besides that, we determined these particular miRNAs as integral components of the GM-CSF-MCPIP-1 axis. Taken together, we identified the novel anti-inflammatory role of MCPIP-1 as a regulator of accumulation and survival of neutrophils that simultaneously promotes an adequate resolution of inflammation.